2016
DOI: 10.1080/09669582.2015.1122015
|View full text |Cite
|
Sign up to set email alerts
|

Comparing levels of resident empowerment among two culturally diverse resident populations in Oizumi, Gunma, Japan

Abstract: While resident empowerment has been a central aspect of the sustainable tourism literature, difficulties of putting the concept into practice have been noted given the heterogeneous nature of communities. "Community" is often divided by kinship, age, gender and ethnicity, and such division may influence the perceptions of empowerment. The goal of this study was to better understand heterogeneous perceptions of empowerment by administering the Resident Empowerment through Tourism Scale within the community of O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 59 publications
3
21
0
Order By: Relevance
“…As Woosnam et al () argue, Japanese residents feel a scarcity of avenues where they can express concerns regarding tourism development issues, and they have little knowledge about tourism development and destination marketing organizations. Therefore, as Maruyama et al () argue, local government and tourism officials should focus on providing ways for Japanese residents to learn about tourism development within Japan and their community and to share any concerns regarding planning and managing for tourism. Maruyama et al () argue that the importance of community involvement is only just being recognized by the Japanese government, so there is much scope for further research to be undertaken in the area of resident attitudes and opinions of tourism development in Japan, and how they might be empowered in discussion and decisions around tourism development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As Woosnam et al () argue, Japanese residents feel a scarcity of avenues where they can express concerns regarding tourism development issues, and they have little knowledge about tourism development and destination marketing organizations. Therefore, as Maruyama et al () argue, local government and tourism officials should focus on providing ways for Japanese residents to learn about tourism development within Japan and their community and to share any concerns regarding planning and managing for tourism. Maruyama et al () argue that the importance of community involvement is only just being recognized by the Japanese government, so there is much scope for further research to be undertaken in the area of resident attitudes and opinions of tourism development in Japan, and how they might be empowered in discussion and decisions around tourism development.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, academics have begun to investigate Japanese resident attitudes towards tourism and tourism development in Japan. Recent research has included an investigation into resident empowerment in tourism development and decision‐making in Japan, including resident empowerment amongst Japanese in a Brazilian community (Boley, Maruyama, & Woosnam, ) and between a dominant ethic group (Japanese) and a minority ethnic group (Brazilian) in Oizumi (Maruyama, Woosnam, & Boley, ). Further, Japanese resident studies have included a focus on ethnic neighborhood and enclave tourism in Japan (Maruyama, Woosnam, & Boley, ; Woosnam, Maruyama, Boley, & Erul, ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of the RETS in an ethnically diverse Japanese setting, including Brazilian and Japanese communities, revealed that Brazilian residents exhibit more social and psychological empowerment than Japanese residents (Boley, Maruyama, & Woosnam, 2015;Maruyama, Woosnam, & Boley, 2016, 2017. Tourism fostered a sense of community spirit and connectedness to others that leads to opportunities to be involved in the community (Boley et al, 2015).…”
Section: Systematic Review Proceduresmentioning
confidence: 99%
“…The level of cohesion between community members mediating the development of social capital can be understood as a measure of social empowerment (Scheyvens 1999). Residents’ perceived levels of social empowerment from tourism are thought to affect their perceptions of the impacts of tourism and their overall support of tourism development (Maruyama, Woosnam, and Boley 2016; Strzelecka, Boley, and Strzelecka 2017).…”
Section: Literature Reviewmentioning
confidence: 99%